(untitled) - Hayek, Friedrich A. (Chicago, 1944)
Contents: the abandoned road; the great utopia; individualism and collectivism; planning and democracy, ....
Keywords: Economic policy,Totalitarianism,Chính sách kinh tế,Chế độ độc tài